2012
DOI: 10.1371/journal.pone.0031376
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Lacks a Vitamin D Independent Physiological Role in Glucose Homeostasis, Bone Turnover, and Steady-State PTH Secretion In Vivo

Abstract: Apart from its function as co-receptor for fibroblast growth factor-23 (FGF23), Klotho is thought to regulate insulin signaling, intracellular oxidative stress, and parathyroid hormone (PTH) secretion in an FGF23 independent fashion. Here, we crossed Klotho deficient (Kl−/−) mice with vitamin D receptor (VDR) mutant mice to examine further vitamin D independent functions of Klotho. All mice were fed a rescue diet enriched with calcium, phosphorus, and lactose to prevent hyperparathyroidism in VDR mutants, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…A vitamin D-free diet (D-diet) has been reported to maintain phosphate homeostasis and improve the kl/kl phenotype89. In this study, we fed kl/kl mice on a D-diet to determine whether the decreased vitamin D level could enhance UUO-induced RTF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A vitamin D-free diet (D-diet) has been reported to maintain phosphate homeostasis and improve the kl/kl phenotype89. In this study, we fed kl/kl mice on a D-diet to determine whether the decreased vitamin D level could enhance UUO-induced RTF.…”
Section: Resultsmentioning
confidence: 99%
“…FGF23, a member of the fibroblast growth factor (FGF) family, is a bone-derived hormone that exerts its function in the kidneys, to help maintain homeostasis in phosphate and vitamin D metabolism by regulating the sodium phosphate co-transporter and the key enzymes for vitamin D metabolism CYP27B1 and CYP24A15678. Similar to FGF23-deficient mice, kl/kl mice also exhibit hyperphosphatemia and an increased serum 1,25 (OH) 2 vitamin D 3 level1, which are suspected to be the primary cause of premature aging because restricting vitamin D intake improves the kl/kl phenotype89. Secreted Klotho is formed via either alternative splicing of the gene or shedding of the extracellular domain into the extracellular space and subsequently into the circulation210.…”
mentioning
confidence: 99%
“…Membrane bound klotho also plays an integral part in the regulation of phosphate, calcium and vitamin D homeostasis in human and mice[2, 5, 8, 84, 136, 190]. Lack of expression in either klotho or FGF23 result in phosphate retention and a premature-aging syndrome in the mouse[94, 101, 128, 146, 147].…”
Section: Commentsmentioning
confidence: 99%
“…Prior studies have focused on the roles of Klotho in chronic renal disorders[37, 74-76, 142, 178, 184, 214], disorders of calcium metabolism[2, 5, 8, 73, 82, 84, 190], hypertension,[33, 123, 132, 175, 197] and aging[49, 93, 96, 109, 187, 191]. Kuro-o et al demonstrated that klotho is also expressed in the placenta; however, of pregnancy complications has not been investigated [96].…”
Section: Commentsmentioning
confidence: 99%
“…Klotho deficiency increases plasma 1,25(OH) 2 D 3 , Ca 2+ and phosphate [18,19] concentration, resulting in vascular calcification [20], growth deficit [2] and rapid aging [2,9,10]. Klotho insufficiency further leads to a wide variety of disorders including hypoglycemia, hearing loss, cardiac arrhythmia, sudden cardiac death, and compromised immune response [1,21,22]. …”
Section: Introductionmentioning
confidence: 99%